Does ultrasound guidance improve the outcomes of arthrocentesis and corticosteroid injection of the knee? - Sibbitt, W.; Kettwich, L.; Band, P.; Chavez-Chiang, N.; Delea, S.; Haseler, Luke; Bankhurst, A. (Taylor & Francis, 2012)
Objective: The present randomized controlled trial compared arthrocentesis of the effusive knee followed by corticosteroid injection performed by the conventional anatomic landmark palpation-guided technique to the same procedure performed with ultrasound (US) needle guidance. Methods: Sixty-four palpably effusive knees were randomized to (i) palpation-guided arthrocentesis with a conventional 20-mL syringe (22 knees), (ii) US-guided arthrocentesis with a 25-mL reciprocating procedure device (RPD) mechanical aspirating syringe (22 knees), or (iii) US-guided arthrocentesis with a 60-mL automatic aspirating syringe (20 knees). The one-needle two-syringe technique was used. Outcome measures included patient pain by the Visual Analogue Scale (VAS) for pain (010 cm), the proportion of diagnostic samples, synovial fluid volume yield, complications, and therapeutic outcome at 2 weeks. Results: Sonographic guidance resulted in 48% less procedural pan (VAS; palpation-guided: 5.8 ± 3.0 cm, US-guided: 3.0 ± 2.8 cm, p < 0.001), 183% increased aspirated synovial fluid volumes (palpation-guided: 12 ± 10 mL, US-guided: 34 ± 25 mL, p < 0.0001), and improved outcomes at 2 weeks (VAS; palpation-guided: 2.8 ± 2.4 cm, US-guided: 1.5 ± 1.9 cm, p = 0.034). Outcomes of sonographic guidance with the mechanical syringe and automatic syringe were comparable in all outcome measures. Conclusions: US-guided arthrocentesis and injection of the knee are superior to anatomic landmark palpation-guided arthrocentesis, resulting in significantly less procedural pain, improved arthrocentesis success, greater synovial fluid yie ld, more complete joint decompression, and improved clinical outcomes. © 2011 Informa Healthcare on behalf of The Scandinavian Rheumatology Research Foundation.